Land Resource Potential for Agricultural Commodity Development in West Kalimantan Province - . HIKMATULLAH; NONO SUTRISNO; ACHMAD HIDAYAT (Jurnal Sumberdaya Lahan, 2008)
West Kalimantan province with total areas of 14.64 million ha has already had spatial database of land resources at scale of 1:250,000 resulted from reconnaissance soil mapping (2004-2007). This database can be used for composing agricultural planing at province level. The area is composed of wetland ecosystem which covers 3,659,736 ha (24.99%), drylands with <15% slopes covers 4,356,790 (29.74%) and >15% slopes covers 6,441,956 ha (44.0%). The coverage of existing landuse for agriculture is only about 13.85% of the total area. In general, the area belongs to wet climate with average annual rainfall varies from 2,663 to 4,191 mm, and belongs to A, B1, and C agroclimatic zones. The area has various kinds of parent materials consisting of alluvium, organic matter deposit, old volcanic rocks, intrusive rocks, sedimentary rocks and metamorphic rocks that formed soil orders of Histosols, Entisols, Inceptisols, Spodosols, Ultisols, and Oxisols, which give variation in their properties. The result of the land resource potential analysis for agricultural commodity development is directed to: (a) land intensification for rice fields covers about 221,381ha, upland food crops (maize, upland rice, legumes, tuber crops) covers 173,581 ha, annual or estate crops (rubber, oil palms, coconut, pepper, and coffea) including fruit crops covers 570,266 ha, and for brackish fishpond covers 7,394 ha, and (b) land extensification for rice fields covers 869,133 ha, upland food crops 1,316,058 ha, estate crops (oil palm, rubber, coconut, pepper, coffea) covers 3,098,269 ha (as first priority at 15-25% slopes) and 1,300,374 ha (as second priority at 25-40% slopes), and for brackish fishponds covers 25,437 ha. The availability of spatial land resource information to develop high economic value of agricultural commodities, especially estate crops, would support establishing growth centre of agribusiness and agroindustry in the area.